The Influence of Principal Instructional Leadership on Teacher Performance: A Literature Review (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This article aims to examine the role of instructional leadership of school principals on teacher performance. The method used in this study is a literature review, with data collection using articles collected in the last 5 years, namely from 2020 to 2024. The reference articles consisted of 20 national and international articles obtained through Google Scholar and Harzing’s Publish or Perish (PoP) with the keywords “instructional leadership” and “teacher performance”. The theoretical benefit of this article is to increase knowledge about instructional leadership and teacher performance, while the practical benefit of this article can be used as a reference for further research. The results of this study show that the role of the principal is very important in instructional leadership because the principal, as the school leader, holds an important position with great responsibility in maintaining and improving the quality of learning in schools. Instructional leadership is a leadership style in which leaders are able to determine a clear school mission, monitor learning plans, and manage learning resources well. Therefore, teacher teaching performance can be improved by improving the instructional leadership performance of the principal. It can be concluded that the instructional leadership of the principal plays a major role in teacher teaching performance.